Comparison of a new image-guided system versus partial coherence interferometry, Scheimpflug imaging, and optical low-coherence reflectometry devices: keratometry and repeatability - Müller, Andreas; Thomas, Bettina C.; Auffarth, Gerd U.; Holzer, Mike P. (Journal of cataract and refractive surgery, 2016)
Purpose - To determine the repeatability of keratometry of the Verion image-guided system and to compare the keratometry (K) values with those of established biometric devices. - Setting - International Vision Correction Research Centre, Department of Ophthalmology, University of Heidelberg, Heidelberg, Germany. - Design - Prospective case series. - Methods - One randomly chosen eye of volunteers was examined with partial coherence interferometry (PCI) (IOLMaster 500), optical low-coherence reflectometry (OLCR) (Lenstar LS 900), a Scheimpflug device (Pentacam HR), and the new image-guided system by the same examiner. None of the eyes had ocular pathology. Three consecutive measurements were performed with the image-guided system and 1 with the other devices. The flat, steep, and average corneal radii; steep axis; and white-to-white (WTW) distance were analyzed and compared. - Results - One hundred twenty-three eyes of 123 volunteers (mean age 37.9 years ± 16.2 [SD]) had valid measurements for all examinations and were available for analysis. The image-guided system measured statistically significant smaller flat, steep, and average corneal radii than the Scheimpflug device, statistically significant larger flat and average corneal radii than the PCI device, and no statistically significant different values than the OLCR device. The measured steep axis did not differ significantly in any comparison. The WTW measurements were significantly higher than those of all other devices. The analysis of repeatability of the image-guided system showed high intraclass correlation coefficients (range 0.919 to 0.997). - Conclusions - The new image-guided system had high repeatability for K, steep axis, and WTW measurements. The WTW measurements with the image-guided system were significantly higher than those using the other devices. - Financial Disclosure - None of the authors has a financial or proprietary interest in any material or method mentioned.